Clinical Practice and Clinical Supervision: Building a Firm Foundation - Chang, Jeff; Mudry, Tanya E.; Hiseler, Lara (Canadian Journal of Counselling and Psychotherapy, 2020)
In this paper, the authors report on the “Foregrounding Clinical Practice and Clinical Supervision” working group of the Canadian Counselling Psychology Conference held on October 26 to 28, 2018, at the University of Calgary. Of the 12 working group participants, nine self-identified as students and three identified as licensed practitioners (two of the practitioners also held academic positions). This group of mostly early-career professionals identified an overarching theme of building a firm foundation for their future practice. Working group members identified three important contributors: the development of a strong, multi-faceted professional identity, including issues of licensure and certification, the interplay between counselling and clinical psychology, and the place of career psychology; the importance of clinical supervision, including the perceived variable quality of supervision and the apparent shortage of practicum placements; and professional role models. The authors provide their perspectives on the issue the working group raised and offer recommendations for counsellor educators and practice leaders.